2019
DOI: 10.1080/13548506.2019.1679846
|View full text |Cite
|
Sign up to set email alerts
|

Using the theoretical domains framework to explore primary health care practitioner’s perspectives and experiences of preconception physical activity guidance and promotion

Abstract: Preconception physical activity is one of the main predictors of continued engagement in physical activity during and after pregnancy and subsequently, improves the health of women and their child.In the UK, guidance states that Primary Care health Professionals (PCPs) should assess and discuss the lifestyle of preconception women, in routine appointments, in order to address potentially modifiable risk factors. However, knowledge and provision of this guidance in the UK is unknown.It is not clear if individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Most studies, regardless of design, identified insufficient time as a prominent barrier to PA promotion/ER use [ 33 – 35 , 38 – 41 , 43 – 45 , 49 ] with the perception that doctors should prioritise other issues within consultations [ 34 36 , 40 , 41 ]. Insufficient time was identified in both primary and secondary care settings: in their study of 231 GPs and GP registrars, Wheeler et al reported that 91% of fully qualified GPs perceived that insufficient time limits them discussing PA [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies, regardless of design, identified insufficient time as a prominent barrier to PA promotion/ER use [ 33 – 35 , 38 – 41 , 43 – 45 , 49 ] with the perception that doctors should prioritise other issues within consultations [ 34 36 , 40 , 41 ]. Insufficient time was identified in both primary and secondary care settings: in their study of 231 GPs and GP registrars, Wheeler et al reported that 91% of fully qualified GPs perceived that insufficient time limits them discussing PA [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interviews with 15 GPs conducted by Kime et al investigated how prepared GPs felt delivering PA advice to patients with diabetes, and found that some GPs felt out of their depth giving PA advice in general, and particularly concerning PA and diabetes [ 40 ]. In their qualitative study of eight GPs in Scotland, Sissons et al found that some lacked confidence in the effectiveness of their advice and felt their guidance on PA for preconception women may be less effective than other information sources [ 34 ]. In a study of 33 doctors with haematological cancer patients, approximately two thirds of the medical professionals felt that they lacked confidence giving PA advice to patients during cancer treatment, and less than half felt confident giving PA recommendations after treatment [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Utilising the TDF for HPs’ views provided a valuable means to understand the individual and organisational determinants of the HPs behaviour and decision-making. Previous research using COM-B and TDF in the PA context appear within the domains of preconception PA guidance and promotion by GPs and community pharmacists, 50 PA among postnatal women, 51 and determinants of PA with overweight/obese pregnant women. 49 This study targeted a more general primary care population with few restrictions in terms of recruitment, and also had the advantage of investigating the views of patients and HPs.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the interviews, the topic list of the interview guide was compiled, which was based on the Theoretical Domains Framework (TDF) and COM-B model. The validated TDF, consisting of 14 domains, was designed to assist healthcare professionals (hereinafter referred to as professionals) to identify their behaviour on the implementation of evidence-based research in daily practices [24] and has been used as such in previous studies [25][26][27]. The COM-B model was designed to identify what needs to change for a behaviour change intervention to be effective and focuses on three components (i.e., 'capability', 'opportunity', and 'motivation').…”
Section: Methodsmentioning
confidence: 99%